2018
DOI: 10.17957/ijab/15.0488
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Indigenous Landraces of Brassica napus based on Morphological and Biochemical Characteristics using Multivariate Techniques

Abstract: In order to assess genetic diversity of Brassica napus L., the seventy indigenous landraces along with two check cultivars (Shiralee and Pakola) were collected from different regions of Pakistan. The said germplasm was evaluated for 25 morphological and biochemical traits under field conditions during 2012 and 2013 at University of Haripur, Pakistan. Significant genotypic variability was observed among the tested landraces of B. napus for majority of traits during both years of studies. Among B. napus germplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In tested cultivars, the results showed that minimum mean numbers of aphid population were observed in cultivar China considered as resistant, while maximum mean numbers of aphid population were observed in cultivar Swabi which was considered as susceptible. The present investigation was similar to Ali et al (2018), who reported that the least numbers of aphid population were recorded on resistant cultivar and maximum aphid populations were recorded on susceptible cultivar Swabi. Therefore, the tested cultivar Swabi is recommended to control substantial aphid abundance from starting the seasons.…”
Section: Yield Of Canola Cropsupporting
confidence: 91%
“…In tested cultivars, the results showed that minimum mean numbers of aphid population were observed in cultivar China considered as resistant, while maximum mean numbers of aphid population were observed in cultivar Swabi which was considered as susceptible. The present investigation was similar to Ali et al (2018), who reported that the least numbers of aphid population were recorded on resistant cultivar and maximum aphid populations were recorded on susceptible cultivar Swabi. Therefore, the tested cultivar Swabi is recommended to control substantial aphid abundance from starting the seasons.…”
Section: Yield Of Canola Cropsupporting
confidence: 91%
“…From the loading plot, it became clear that parameters previously used as a substitution for yield/plant, such as the seeds/pod, plant height, pods per plant, TSW and raceme length [ 55 , 56 ] were significantly associated with yield/plant in this study ( Fig 5 ) but not with silique length. These results suggest that commercially-used proxy, such as silique length, may not be the significant gauge of yield for breeding and selection purposes [ 56 , 57 ]. Silique length had negative relationship with other morpho-biochemical; yield linked parameters except TSP.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al (2002), also found significant result for days to flowering and maturity. Days to maturity were found significant in all of the genotypes (Ali 2018).…”
Section: Resultsmentioning
confidence: 89%
“…low erucic acid and glycosinolate contents which narrowed down the genetic base (Friedt and Snowdon 2009). Breeding for agronomic and economic values tends to bias the exploitation of genetic variation (Ali et al 2018). Therefore, it is necessary to continuously integrate diverse germplasm into the breeding process in order to maintain a high level of genetic diversity.…”
Section: Introductionmentioning
confidence: 99%